Crustáceos ectoparásitos y epibiontes de ballenas jorobadas, Megaptera novaeangliae (Cetacea: Balaenopteridae) en el Pacífico colombiano - Avila, Isabel Cristina (2011)
We recorded three species of crustacean ectoparasites and epibionts in two calves and four adults of humpback whale (Megaptera novaeangliae) that in the breeding season 2010 visited PNN Gorgona and Bahía Málaga, Colombian Pacific: the amphipod Cyamus boopis and the barnacles Coronula diadema and Conchoderma auritum. These crustaceans adhere to calves and adults and are present in the caudal fin, dorsal fin, back of the body (near the blowhole) and ventral side of the lower jaw. Ectoparasites and epibionts recorded here may influence the movement, feeding and behavior of whales. We found a calf of no more than three months of age with epibionts: epibionts seem to attach to whales in tropical waters, most likely in Colombian waters.